Study on the mechanism of cadmium chloride pollution accelerating skin tissue metabolism disorder, aging and inhibiting hair regeneration - Weibin Du; Weibin Du; Yi Dong; Zhenwei Wang; Zhenwei Wang; Sai Yao; Sai Yao; Meijiao Wang; Jinjun Ji; Hongfeng Ruan; Hongfeng Ruan; Renfu Quan; et al. (Frontiers Media S.A., 2022)
Drinking water contaminated by Cd2+ is one of the main pathways for Cd to enter the body. The skin barrier is destroyed when the skin is contaminated by environmental Cd2+, however, the detailed mechanism by which Cd2+ induces skin metabolic disorder, and senescence and affects hair regeneration is not completely understood. In this study, 18 C57BL/6 mice were randomly divided into a Control group, a Low-dose group, and a High-dose group with 6 mice in each group, and intragastrically administered with different concentrations of cadmium chloride once a day, respectively. After 1 month of intervention, the skin tissues on the back of mice were collected for non-targeted metabolomics analysis, and the related proteins were detected by immunofluorescence assay. Non-targeted metabolomics analysis result showed that compared with the Control group, there were 29 different metabolites, mainly including lysophospholipids, fatty acids, and bile acids, in the Low-dose group, and 39 differential metabolites in the High-dose group, in addition to the above compounds, there were more amino acid compounds, and most of the metabolites had a reduced response after administration. Immunofluorescence assay result showed that the higher the concentration of cadmium chloride led to the more obvious the proliferation inhibition and apoptosis promotion effects of skin cells, and the more significant damage to hair follicle stem cells. Thus, our findings demonstrate that cadmium chloride pollution can accelerate skin metabolism disorder, and aging and impair hair regeneration.